THE GEOLOGICAL RELATIONSHIPS OF THE KOROSTEN COMPLEX ROCKS ON THE EXAMPLE OF THE MALIN RAPAKIVI GRANITE MASSIF - BILAN, O.; MYTROKHIN, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The geological relationships of rapakivi granites and basic rocks of the Korosten complex has been studied in Malin rapakivi massif. The attempt of agreement of the geological dates with isotopic ages has been undertaked. Autors conclude that main intrusive phase of rapakivi granites has more young age than anorthosites of first and second intrusive phase of Fedorovka massif. The gabbroids of third intrusive phase are the same age as rapakivi granites. Magmatic mixing of the acid and basic magmas caused development of the monzonitic rocks among the gabbroids.